STUDY ON FOSTERING A STRONG NATIONAL IDENTITY AND EFFECTIVE STRATEGIES FOR IMPLEMENTING NATIONAL VALUES INSTRUCTION AMONG SENIOR SECONDARY SCHOOLS TEACHERS IN KANO STATE, NIGERIA - SHEHU, BELLO (Sokoto Educational Review, 2025)
This study examined strategies for fostering a strong national identity and effectively implementing national values instruction among senior secondary school teachers in Kano State, Nigeria. Guided by five research objectives, two research questions, and three null hypotheses, the study used a descriptive survey design and a sample of 384 teachers selected through simple random, stratified proportionate, and systematic sampling techniques. The researcher-designed instrument, the “Teachers National Identity and National Values Instruction Questionnaire (TNINVIQ),” was validated by experts and demonstrated a reliability coefficient of 0.78. Data analysis involved frequency, percentage, mean, standard deviation, one-way analysis of variance, Pearson correlation, and regression analysis. Findings indicated that teachers perceive the implementation of national identity and values instruction as relatively high. However, challenges such as training needs, lack of resources, government policies, and cultural barriers significantly impact the implementation process. The study also found that demographic factors, such as age and experience, influence teachers' perceptions, with older and more experienced teachers reporting higher levels of national identity and values instruction. Lack of resources, cultural barriers, and training needs were negatively correlated with the implementation of national values instruction. The study concluded that effective strategies significantly impact national identity. Recommendations include developing targeted training programs to address teachers’ needs and allocating sufficient resources to schools to enhance the implementation of national values instruction.